Circ_0005320 promotes oral squamous cell carcinoma tumorigenesis by sponging microRNA-486-3p and microRNA-637. Issue 1 (1st January 2022) - Zheng, Xiaotao; Du, Fang; Gong, Xuepeng; Xu, Ping
ABSTRACT: Circ_0005320 was found to be elevated in oral squamous cell carcinoma (OSCC) and accelerated OSCC progression. Here, the potential mechanism of circ_0005320 in OSCC tumorigenesis was explored. The quantitative real-time polymerase chain reaction (qRT-PCR) assay was used to detect the expression of circ_0005320, miR-486-3p, and miR-637. In vitro assays were conducted using cell counting kit-8, colony formation, transwell, angiogenesis, and flow cytometry assays. The targeting relationship between microRNA (miR)-486-3p and miR-637 or circ_0005320 was confirmed using the dual-luciferase reporter and RNA immunoprecipitation (RIP) assays. The Janus Kinase 2/Signal Transducer and Activator of Transcription 3 (JAK2/STAT3) pathway-related proteins were analyzed using Western blot. The murine xenograft model was established to perform in vivo assay. Circ_0005320 expression was higher in OSCC tissues and cells. Knockdown of circ_0005320 suppressed OSCC cell growth, migration, invasion, and induced cell apoptosis in vitro, as well as impeded tumor growth in vivo. Mechanistically, miR-486-3p or miR-637 were confirmed to be a target of circ_0005320. Moreover, the inhibitory effects of circ_0005320 silencing on OSCC growth were reversed by the inhibition of miR-486-3p or miR-637. We also found that circ_0005320-miR-486-3p/miR-637 axis mediated the activation of JAK2/STAT3 pathway. This study revealed a novel regulatory network of circ_0005320-miR-486-3p/miR-637 axis in OSCC progression, suggesting that circ_0005320 might be a potential biomarker and therapeutic target for OSCC.